Association between screen time and hyperactive behaviors in children under 3 years in China - Wu, Jian-Bo; Yin, Xiao-Na; Qiu, Shuang-Yan; Wen, Guo-Ming; Yang, Wei-Kang; Zhang, Jing-Yu; Zhao, Ya-Fen; Wang, Xin; Hong, Xiao-Bing; Lu, DaLi; Jing, Jin (Frontiers in Psychiatry, 2022)
ABSTRACT Background Screen time during early life has increased dramatically among Chinese children. Excessive screen time has raised growing concerns about the neuropsychological development of children. However, the effects of screen exposure on early life and the boundary between screen time and hyperactive behaviors has not been studied. We examined associations between screen time and hyperactive behaviors in children under the age of 3 years using data from the Longhua Children Cohort Study. Methods A cross-sectional study was conducted among 42,841 3-year-old children from Longhua District, Shenzhen. Information on socio-demographic characteristics, children's annual screen time since birth, and hyperactive behaviors (measured by the Conners Parental Symptom Questionnaire) was collected through self-administered structured questionnaires completed by the primary caregiver. A series of logistic regression models assessed the association between screen time and hyperactive behaviors. Results The average daily screen time of children under the age of 3 years was 55.83±58.54 minutes, and screen time increased with age. Crossover analysis found that the earlier the screen exposure, the greater the risk of hyperactive behaviors (P < 0.05). Using binary logistic regression model, after controlling for confounding factors, the study found that more screen time increased the risk of hyperactive behaviors. For children aged 0–3 years with daily screen time exceeding 90 minutes, 120 minutes, 150 minutes and 180 minutes, the risk values for hyperactive behaviors were 1.98 (95% confidence interval [CI]: 1.05, 3.78), 2.71 (95 %CI:1.38, 5.30), 3.17 (95% CI: 1.50, 6.65), and 4.62 (95% CI: 2.45, 8.71), respectively. Conclusion Early screen exposure may increase hyperactive behaviors in children under the age of 3 years. More than 90 minutes of screen time per day in children under 3 years was associated with hyperactive behaviors. The findings support the importance of screen time interventions for children under 3 years.